The Effect of Self Confidence on Job Readiness - Ristiani Ristiani; Farah Putri Wenang Lusianingrum (Journal of Applied Business, Taxation and Economics Research, 2022)
Job readiness can be one of the characteristics that show the quality of a worker. Final-year undergraduate students need to prepare themselves to work, and new undergraduate students start from 18. They have entered early adulthood. The research objective was to determine whether there was an effect on undergraduate student self-confidence in the age group during the fourth semester of their lecture on their employability. This research is a survey type quantitative method, with primary data obtained through questionnaires. Determination of the sample using purposive sampling technique with the criteria of undergraduate students taking Personality Development courses in the semester. The number of respondents was 294 students. The results showed an effect of self-confidence on job readiness, amounting to 24.4%. As much as 75.6% of job readiness is influenced by other variables not studied. Educational institutions or practitioners involved in work preparation activities can prepare individual development plans through various programs starting with identifying each individual himself.